2019
DOI: 10.1590/1414-431x20198596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three PET methods to assess peritoneal membrane transport

Abstract: The peritoneal equilibration test (PET) is the most widespread method for assessing water and solute transport across the peritoneal membrane. This study compared three methods: traditional PET (t-PET), mini-PET, and modified PET (mod-PET). Non-diabetic adults (n=21) who had been on peritoneal dialysis (PD) for at least three months underwent t-PET (glucose 2.5%-4 h), mini-PET (glucose 3.86%-1 h), and mod-PET (glucose 3.86%-4 h) to determine dialysate-to-plasma concentration ratio (D/P) for creatinine and dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It may also provide information on total ultrafiltration and solute transport [ 17 ]. Although the peritoneal equilibrium test has been used to elucidate the properties of the peritoneum [ 18 ], however, it cannot adequately predict the dynamics of the peritoneal fluid or the optimal retention time because the total ultrafiltration of peritoneal dialysis depends not only on the removal of peritoneal fluid but also on the absorption of peritoneal fluid [ 19 ]. So it is difficult to predict the time to reach the maximum ultrafiltration volume (UFVmax) and the maximum ultrafiltration volume.…”
Section: Discussionmentioning
confidence: 99%
“…It may also provide information on total ultrafiltration and solute transport [ 17 ]. Although the peritoneal equilibrium test has been used to elucidate the properties of the peritoneum [ 18 ], however, it cannot adequately predict the dynamics of the peritoneal fluid or the optimal retention time because the total ultrafiltration of peritoneal dialysis depends not only on the removal of peritoneal fluid but also on the absorption of peritoneal fluid [ 19 ]. So it is difficult to predict the time to reach the maximum ultrafiltration volume (UFVmax) and the maximum ultrafiltration volume.…”
Section: Discussionmentioning
confidence: 99%
“…40,[47][48][49][50] In a study comparing traditional PET, modified PET and mini-PET, Romani et al used the dialysate-to-plasma concentration ratio for creatinine (D/P creatinine) and the dialysate-to-baseline dialysate concentration ratio for glucose (D/D0 glucose) to assess and compare the small-solute transfer profile of 21 patients undergoing PD. 51 The authors found D/P creatinine measurements among patients undergoing modified PET and traditional PET to be comparable, suggesting that modified PET is a method of PET that provides additional evaluation of UF and free water transfer without compromising on the evaluation of small solute transfer. On the other hand, mini-PET was observed to lack equivalence to traditional PET in its evaluation of small solute transfer.…”
Section: What Are the Different Forms Of The Peritoneal Equilibration...mentioning
confidence: 95%